PENGARUH PRODUK, HARGA DAN KUALITAS PELAYANAN, TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS UPSTREET PALOPO) - Ayu Anugrah; Adi Muhammad Fatwah M, Rudianto, Nurjannah (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to analyze the effect of product price and service quality on purchasing decisions (Case study of Upstreet Palopo). Sampling method by taking The sampling technique in this study using "Random Sampling". The number of samples in this study were 50 respondents from an unknown population. Data collection techniques using observation, questionnaire and documentation. Data processing techniques with a regression system with the help of SPSS software (Statistical Package for the Social Sciences) data analysis techniques used are validity test, reliability test, multiple linear regression test, determinant coefficient test, t test (partial) and F test (simultaneous). The results of this study concluded that service quality has a positive and significant impact on purchasing decisions on Upstreet Palopo. There is an effect of price on purchasing decisions, the better the product, price and quality of service provided, the more satisfied consumers will be, the more positive and significant effect this will have on purchasing decisions (study of the Upstreet Palopo case)